Implementation of corporate culture moral values (Akhlak) for PT Pegadaian's competitive advantage - Taufan Maulamin; Antoni Ludfi Arifin; Resista Vikaliana; R. Swasono Amoeng Widodo (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
PT Pegadaian continues to show positive performance throughout the 2020 fiscal year, an increase from 2019. This shows that PT Pegadaian can compete and develop during the Covid-19 pandemic. In addition, to increase competition with other companies, human resources with competitive advantages are needed which are assessed through corporate culture and AKHLAK values. The purpose of this research is to see how the influence of corporate culture and AKHLAK values on the competitive advantage of PT Pegadaian. The research samples taken were employees of PT Pegadaian throughout Indonesia, namely 250 samples. Analysis method Structural Equation Model (SEM) program through Smart PLS software. the results of the study show that corporate culture has a positive and significant impact on company excellence, corporate culture also has a positive and significant impact on AKHLAK values. AKHLAK values do not have a significant influence on competitive advantage nor are they able to mediate the influence of corporate culture on competitive advantage.